The anti-inflammatory, anti-ulcer activities and phytochemical investigation of Cucumis melo L. cv. Ismailawi fruits. Issue 24 (17th December 2021) - Moustafa, Sherifa F.; Gabr, Nagwan M.; Zaki, Jaky T.; El Awdan, Sally A.; Mina, Suzan A.
Abstract: This study aims to evaluate the anti-inflammatory and anti-ulcer activities of Cucumis melo L. cv. Ismailawi fruits, as well as the investigation of the phenolic content and lipoidal matter composition via high performance liquid chromatography and gas chromatography coupled to mass spectrometry respectively. Both the petroleum ether and defatted methanol extracts of the fruit pulp showed 63.13% and 54.97% decrease in oedema volume respectively after 4 h in comparison to indomethacin standard drug. Both the petroleum ether extract and ethyl acetate fractions at a dose (200 mg/kg) showed significant anti-ulcer activity decreasing both ulcer number and severity in comparison to ranitidine as standard drug. Histopathological investigation further confirmed these results. Moreover; this is the first report for the investigation of the phenolic content and the lipoidal matter of Cucumis melo L. cv. Ismailawi fruits where methyl palmatate, gallic acid and rutin represented the major detected components. Graphical Abstract: UF0001